i-gel™ vs. AuraOnce™ laryngeal mask for general anaesthesia with controlled ventilation in paralyzed patients - Donaldson, William; Abraham, Alexander; Deighan, Mairead; Michalek, Pavel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2011)
AIMS: The i-gel™ and the AuraOnce™ laryngeal mask are supraglottic airway devices used for airway management during general anaesthesia. Both devices are cheap, disposable and widely used. They may be used with both spontaneous and controlled ventilation. This study compared differences in the seal and peak pressures, and postoperative complications in these devices when used in paralyzed patients under controlled ventilation. METHODS: A prospective randomized trial was designed to compare the i-gel™ and the AuraOnce™ in paralyzed adult patients under conditions of controlled ventilation. Two hundred and four patients (ASA class 1-3, age 18-89, weight 46-115 kg) were enrolled in the study. Standardized anaesthesia (fentanyl, propofol and sevoflurane in air-oxygen) was administered including neuromuscular blockade. The primary outcome measure was the difference in seal airway pressures between the two devices. Secondary outcome measures included peak airway pressures, insertion data and postoperative profiles--the incidence of sore throat, swallowing difficulties, numb tongue, hearing difficulties, neck pain, nausea and vomiting. RESULTS: First time insertions were 85.6% (i-gel) and 82% (AuraOnce) with overall success rates 96.3% (i-gel) and 94.2% (AuraOnce) (p=0.54). Average insertion times were 11.0 s (i-gel) and 11.6 s (AuraOnce) (p=0.19). Seal pressures were 30.4 cmH(2)O (i-gel) and 27.8 cmH(2)O (AuraOnce) (p=0.007). Peak pressures were 15.3 cmH(2)O (i-gel) and 15.6 cmH(2)O (AuraOnce) (p=0.57). Traumatic insertion occurred in 5.8% of i-gel™ and 2% of AuraOnce™ insertions. The overall incidence of postoperative complications was low, with the i-gel™ causing less sore throat and difficulty swallowing at 24h. Conclusion. Both devices provided effective seals for ventilation under positive pressure. I-gel™ may be a better alternative for the procedures with controlled ventilation because of higher seal pressures and lower incidence of sore throat postoperatively.
Keywords: Anesthesia, General; Humans; lidé středního věku; celková anestezie; nervosvalová blokáda; Intermittent Positive-Pressure Ventilation; Female; Aged; mladý dospělý; dospělí; Disposable Equipment; Neuromuscular Blockade; senioři; lidé; Adult; Laryngeal Masks; ženské pohlaví; Male; Middle Aged; laryngální masky; ventilace umělá s přerušovaným přetlakem; Aged, 80 and over; Young Adult; senioři nad 80 let; vybavení k jednorázovému použití; mužské pohlaví